CHI '02 Extended Abstracts on Human Factors in Computing Systems 2002
DOI: 10.1145/506443.506599
|View full text |Cite
|
Sign up to set email alerts
|

In-car cell phone use: mitigating risk by signaling remote callers

Abstract: Research has linked in-car cell phone use with automobile accidents. We explore a signaling method that could mitigate that risk. We show in a first experiment how remote cell phone callers were induced to speak less during critical driving periods, and, in a second experiment, how driving performance in a simulator improved when callers reduced conversation levels during critical driving periods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 2 publications
1
10
0
Order By: Relevance
“…An early investigation of intervening phone calls in certain situations has been conducted by Manalavan et al [11]. Using various auditive signals, they provided context information to the remote caller and found that this could induce the caller to speak less.…”
Section: Related Workmentioning
confidence: 99%
“…An early investigation of intervening phone calls in certain situations has been conducted by Manalavan et al [11]. Using various auditive signals, they provided context information to the remote caller and found that this could induce the caller to speak less.…”
Section: Related Workmentioning
confidence: 99%
“…Could we provide callers with contextual information about the road and traffic? In a previous paper [14], we proposed that if remote cell phone callers had some road and traffic information such as that available to passengers who are monitoring the road, callers might moderate or time their conversations so as to reduce the disruptiveness of conversation on the driver. In one experiment, focused on remote callers, we tested whether participants, acting as remote callers to a driver, would moderate their conversational behavior if they were reminded of a driver's road situation.…”
Section: Providing Traffic Context Information For Callersmentioning
confidence: 99%
“…Our findings raise the question of whether push-to-talk cellular radios can offer benefits over telephony when users are performing tasks such as driving. Researchers have suggested that communication channels may be modified to mitigate the risk of drivers being distracted by them (Manalavan et al, 2002). Mobile phones provide an ongoing connection, in which both parties generally are expected to be fairly responsive.…”
Section: From Fieldwork To Designmentioning
confidence: 99%